Onset of Appearance and Potential Significance of Telocytes in the Developing Fetal Lung. (October 2019) - Awad, Mahmoud; Gaber, Wafaa; Ibrahim, Dalia
Abstract: CD34, vimentin, and vascular endothelial growth factor immunohistochemical analysis and electron microscopic tools were employed to record the initial appearance of telocytes (TCs) and stage-by-stage variations in TC localizations in the developing rabbit lung. TCs could not be identified in the primitive embryonic lung until day 18 of gestation. In the pseudoglandular lung, CD34 + TCs had been recorded under the cartilage of the main bronchus, in the wall of large-sized pulmonary vessels and large epithelial tubes. In the canalicular phase, TCs could be demonstrated in the smooth muscle layer of the bronchioles including the terminal ones. The strength of CD34 immunoreactive signals had been amplified by age until the day of parturition. Ultrastructurally, TCs consisted of a tiny body and exceptionally long telopodes (Tps). The Tp consisted of alternating thin segments (podomers) and dilated ones (podoms). The Tp sometimes branched with a dichotomous pattern. TCs interconnected in a network either by homocellular junctions with neighboring TCs or by heterocellular junctions with smooth muscle cells and alveolar cells. Collectively, early detection of TCs in pulmonary vessels suggests a potential role for TCs in their angiogenesis. For the lung tissue, TCs seem to be involved in the regulation of lung histogenesis.